Examining women’s access to justice when using traditional dispute resolution mechanisms to secure their land rights in Kenya - Sifuna, Cynthia Nabwile (Strathmore University, 2021)
The crux of the study was to assess the effectiveness of traditional dispute mechanisms (hereinafter, TDRMs) in facilitating women’s access to justice when securing their land rights in land disputes. The objectives were therefore to assess the status quo regarding the nature and functioning of TDRMs, to analyze the effectiveness of TDRMs in improving access to justice for women with regard to safeguarding their land rights by asking the African woman question and to recommend practical ways that state and non-state actors can apply substantive equality to remove impediments to women accessing justice using TDRMs to secure their land rights.
Land in Sub-Saharan Africa is considered to be the most important asset as it carries with it social, economic, political, cultural and even religious importance.1 Its permanence and durability, which very few other assets have, set it apart in its intergenerational stability.2 Due to its status and far reaching impacts, securing a land title and proper protection of land rights is paramount. Traditional Dispute Resolution Mechanisms (TDRMs) have been championed by the transformative spirit of the 2010 Constitution of Kenya3 and are hailed for improving access to justice.4 While this can be argued to be true prima facie, the experiences of women in the grassroots, with the customary laws upon which these TDRMs are founded, beg probing into the accessibility of justice for this vulnerable group when trying to secure their land rights.